Effect of tactile kinesthetic stimulation on preterm infants’ weight and length of hospital stay in Khartoum, Sudan - Ahmed, Ragaa G. (Saudi Med J, 2015)
OBJECTIVES: To determine the effect of 7 days tactile kinesthetic stimulation (TKS) on preterm infants’ weight and hospital stays in Khartoum State, Sudan. METHODS: This is a quasi-experimental study, it was conducted in 4 hospitals between January and June 2013, Khartoum, Sudan, and it involved 160 preterm infants randomly assigned into the case and control groups (80 neonates in each). Preterm infants in the control group received routine nursing care, while preterm infants in the case group received TKS for 3 periods, 15 minute per day for 7 constitutive days, in addition to routine care. Data was collected using a structured self-designed and validated questionnaire, checklist, and weighting scale. Weight gain and hospital stay were compared between the 2 groups. RESULTS: Over the constitutive 7 days, the case group gained significantly more weight (1071gm versus 1104gm) compared with the control group (1077gm versus 1084gm) (1084.55±90.74) who gained only 6.9gm within the same 7 days without TKS treatment. The mean difference in weight gain was significant (p=0.00). The hospital stay for preterm infants in the case group was significantly shorter (18.05±9.36 versus 25.47±10.25; p=0.00). CONCLUSION: Tactile kinesthetic stimulation for preterm infants has a beneficial effect on weight gain and earlier discharge from hospital, which are sequentially efficient and cost effective.